The impact of public R&D support on firms' patenting - Brita Bye; Marit Klemetsen; Arvid Raknerud (Statistics Norway, Research Department, 2019)
We examine the impact of both R&D tax credits and direct R&D subsidies on Norwegian firms' patenting. Whereas direct subsidies are aimed at projects with low private and high social return, tax credits do not discriminate between projects or technologies. We find that both direct subsidies and tax credits have significant positive effects on patenting. However, the magnitude of the effects depend critically on the firms' pre-treatment characteristics. In particular, the statistically significant estimates are all related to firms with no patent applications prior to obtaining support. Moreover, we estimate that direct subsidies have triggered at least three times as many granted patents per NOK million of support compared to tax credits. Our results suggest that R&D support should be directed to promote innovations at the extensive margin, i.e. to firms with a high potential of becoming innovative rather than to firms with a record of being innovative. Moreover, as targeted subsidies generate more innovations, society would benefit from distributing more of the subsidies to priority areas.
Keywords: C33; C52; D24; O38; 330; Patenting; R&D policy; Treatment effects; Stratification; Matching; Poisson regression